Attitudes towards vaccination against COVID-19 during pregnancy and its determinants among people of reproductive age - Chenyuan Qin; Yansheng Ding; Min Liu; Jue Liu (Human Vaccines & Immunotherapeutics)
The attitudes of reproductive-age individuals toward COVID-19 vaccination during pregnancy are still not well understood. We aimed to explore the attitudes toward COVID-19 vaccines during pregnancy and the determinants among the Chinese reproductive-age population. An anonymous cross-sectional study was conducted in China from July 4 to August 11, 2023. Structured questionnaires on vaccine hesitancy during pregnancy, socio-demographic characteristics, behavior characteristics, health-related factors, and mental health status were sent online to reproductive-age individuals (both males and females). Among 2966 participants of reproductive age, 86.9% exhibited significant hesitancy toward receiving the COVID-19 vaccine during pregnancy. Participants of older age (30–34: aOR = 1.71, 95% CI: 1.62–2.52; 35–39: aOR = 1.72, 95% CI: 1.11–2.66), nonsmokers (aOR = 1.42, 95% CI: 1.07–1.89), with a longer duration since their last COVID-19 vaccination (aOR = 2.37, 95% CI: 1.20–4.70), and exhibiting marked pandemic fatigue (moderate: aOR = 1.98, 95% CI: 1.56–2.52; high: aOR = 3.49, 95% CI: 2.41–5.05) were prone to refuse COVID-19 vaccines during pregnancy. The presence of generalized anxiety disorder may push the vaccination (aOR = 0.75, 95% CI: 0.57–0.99). The top three reasons for hesitation were concerns about the adverse health effects of vaccines on pregnant women (77.72%), fetuses (72.13%), and newborns/infants (58.77%), respectively. Therefore, under the context of the existing circumstances and the WHO’s encouragement, this study provides data support for possible future policy changes and emphasizes the importance of public health strategies.